Comparison of TiN and TiAlN as a diffusion barrier deposited by atomic layer deposition - Kim, JY; Kim, HK; Kim, Y; Kim, YD; Kim, WM; Jeon, H (KOREAN PHYSICAL SOC, 2002)
We deposited the TiN and the TiAlN films by using the atomic layer deposition (ALD) method with tetrakis-ethylmethyl-amido-titanium (TDMAT) as the Ti precursor, dimethylaluminum-hydride-ethylpiperidine (DMAH-EPP) as the Al precursor, and NH3 as the reactant gas. The composition of the TiN film exhibited stoichiometric TiN, which was almost 1:1 of Ti:N. However, the Ti to Al ratio in the TiAlN film was less than unity. The carbon impurity content in the TiN and the TiAlN films deposited at 200degreesC was below 5 at.%. The growth rates of the TiN and the TiAlN films obtained with this ALD system were about 0.8 and 1.25 Angstrom per cycle. In case of the TiN films, etch pits started to appear when the sample was annealed at 500degreesC while in the TiAlN film they started to appear at 700degreesC.